Is physical activity still the key to treating obesity? - semaglutide, a new position among therapies - Karolina Makowska; Marta Billewicz; Aleksandra Marczyk; Laura Lis (Nicolaus Copernicus University in Toruń, 2024)
Obesity is a condition characterized by excessive and abnormal accumulation of fat tissue. It disrupts energy homeostasis, leading to severe health problems. Physical activity is a significant part of reducing obesity. If sport activities are not enough, pharmacological management may be needed. One of pharmacological approaches to obesity treatment is a use of semaglutide. It is a glucagon-like peptide 1 receptor agonists (GLP-1RAs) approved for the treatment of type 2 diabetes. Semaglutide presents many pleiotropic effects and has an impact on several organ systems, such as cardiovascular, digestive, or nervous systems. Clinicals should remember about semaglutide's complex mechanisms of actions and different adverse effects.